Impact of Brewing Methods on Total Phenolic Content (TPC) in Various Types of Coffee - Olechno, Ewa (Molecules, 2020)
Coffee is a widely consumed beverage, both in Europe, where its consumption is highest, and on other continents. It provides many compounds, including phenolic compounds. The aim of the study was to assess the effect of various brewing methods on the total phenolic content (TPC) in the infusion. Research material comprised commercially available coffees: Instant Arabica and Robusta, freshly ground Arabica and Robusta (immediately prior to the analysis), ground Arabica and Robusta, decaffeinated Arabica, and green Arabica and Robusta. The following preparation methods were used: Pouring hot water over coffee grounds or instant coffee, preparing coffee in a percolator and using a coffee machine. Additional variables which were employed were water temperature (90 or 100 °C) and its type (filtered or unfiltered). In order to determine the impact of examined factors, 225 infusion were prepared. Total phenolic content was determined by the spectrophotometric method using the Folin-Ciocalteu reagent and the obtained results were expressed in mg gallic acid (GAE) per 100 g of brewed coffee. The highest value was obtained for 100% Arabica ground coffee prepared in a coffee percolator using unfiltered water at a temperature of 100 °C: 657.3 ± 23 mg GAE/100 g of infusion. High values were also observed for infusions prepared in a coffee machine, where the highest TPC value was 363.8 ± 28 mg GAE/100 g for ground Arabica. In turn, the lowest TPC was obtained for Arabica green coffee in opaque packaging, brewed with filtered water at a temperature of 100 °C: 19.5 ± 1 mg GAE/100 g of infusion. No significant effect of temperature and water type on the TPC within one type of coffee was observed. Due to its high content of phenolic compounds, Arabica coffee brewed in a coffee percolator should be the most popular choice for coffee drinkers.